Stakeholders’ Perception of Vision, Mission, Objectives, and its Implications on Curriculum Development - Khoirurrijal, Khoirurrijal (Institut Agama Islam Negeri (IAIN) Metro, 2023)
This study aimed to find and analyse stakeholders' perceptions regarding formulating the vision, mission, and objectives of the Postgraduate of Arabic Language Education Masters Program at IAIN Metro and its implications on curriculum development. This research was field research with a qualitative descriptive approach using observation, interview and documentation techniques. The results of the study show that: (a) The scope of the vision is not only at the regional and national levels but also international; (b) The language of the mission should be formulated operationally so that it can be immediately understood and implemented without further guesswork; (c) Vision to accommodate technological developments; (d) To place faith and piety at the beginning of the vision and be actualised in the mission; (e) The implication of the formulation of the vision, mission and objectives on curriculum development is that the content of the material in the curriculum already represents the vision.